Penerapan Inovasi Augmented Reality dalam Rangka Digital Entrepreneurship pada UMKM di Kota Bandung Jawa Barat - Marcelita, Faldiena; Novianty, Inna; Sinaga, Antonya Rumondang; Sayekti, Ayutyas (Penerbit Widina, Widina Media Utama, 2025)
Digital transformation encourages micro, small, and medium enterprises (MSMEs) to adopt innovative technologies to remain competitive in the modern business ecosystem, including the use of Augmented Reality (AR) as an interactive promotional medium. This study aims to enhance the digital entrepreneurship capacity of MSMEs in Bandung City through the implementation of AR as a technology-based immersive marketing strategy. The program was carried out through a series of training activities covering an introduction to digital entrepreneurship concepts, basic AR principles, hands-on AR content creation, publication of AR-based Android applications on the Play Store, and mentoring for AR integration into MSME marketing platforms. The methods included assessing MSME needs, conducting technical training, facilitating strategic discussions on digital marketing, and evaluating program effectiveness through pre–post test surveys. The results indicate an improvement in participants’ digital understanding and skills, reflected in an increase in evaluation scores from 12 to 13, as well as their ability to produce and implement AR content for promotional purposes. The implementation of AR proved to enhance MSMEs’ readiness to adopt digital technologies and opened opportunities for more engaging and consumer-adaptive marketing models. Overall, this study concludes that AR is a strategic tool capable of strengthening the digital transformation of MSMEs and contributes significantly to the development of a more creative, competitive, and sustainable digital entrepreneurship ecosystem.ABSTRAKTransformasi digital mendorong pelaku UMKM untuk mengadopsi teknologi inovatif agar mampu bersaing dalam ekosistem bisnis modern, termasuk pemanfaatan Augmented Reality (AR) sebagai media promosi interaktif. Penelitian ini bertujuan untuk meningkatkan kapasitas digital entrepreneurship UMKM di Kota Bandung melalui penerapan AR sebagai strategi pemasaran digital berbasis teknologi marketing imersif. Kegiatan dilakukan melalui serangkaian pelatihan yang mencakup pemahaman konsep kewirausahaan digital, pengenalan dasar-dasar AR, praktik pembuatan konten AR, hingga publikasi aplikasi AR berbasis Android ke Play Store, serta pendampingan integrasi AR dalam media pemasaran UMKM. Metode pelaksanaan meliputi pemetaan kebutuhan UMKM, pelatihan teknis, diskusi strategis pemasaran digital, dan evaluasi efektivitas program melalui survei pre–post test. Hasil menunjukkan peningkatan pemahaman dan keterampilan digital peserta, yang ditandai dengan kenaikan skor evaluasi dari 12 menjadi 13 serta kemampuan peserta menghasilkan dan menerapkan konten AR untuk kebutuhan promosi. Implementasi AR terbukti meningkatkan kesiapan UMKM dalam memanfaatkan teknologi digital serta membuka peluang model pemasaran inovatif yang lebih menarik dan adaptif terhadap perilaku konsumen. Secara keseluruhan, kegiatan ini menyimpulkan bahwa AR merupakan alat strategis yang mampu memperkuat transformasi digital UMKM dan memberikan kontribusi signifikan bagi pengembangan ekosistem kewirausahaan digital yang lebih kreatif, kompetitif, dan berkelanjutan.